2014
DOI: 10.1017/s1742758414000150
|View full text |Cite
|
Sign up to set email alerts
|

Development of a larval diet for the South American fruit fly Anastrepha fraterculus (Diptera: Tephritidae)

Abstract: Mass-rearing protocols must be developed, in particular, a cost-effective larval diet, to implement the sterile insect technique against Anastrepha fraterculus (Wiedemann).The key elements of this diet are the optimal nutrients and their concentrations, diet supports or bulking agents, and the pH of the diet. To improve the currently used formulation and develop a more cost-effective diet, in the present study, we evaluated various supports, sugar contents, nutrient proportions and pH levels. Egg-to-pupa recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
2
19
0
4
Order By: Relevance
“…For both species of fruit fly, the smaller viability of the larval and pupae stage observed when larvae were kept on diet with pH 2.0, but differing from the diet with pH 3.0, is similar to results reported for Bactrocera invadens Drew, Tsuruta & White, 2005 (Diptera: Tephritidae) using liquid diet with pH 3.5 Ekesi et al (2014). Vera et al (2014) evaluated diets for A. fraterculus with addition of ascorbic, citric and lactic acid and found that, irrespective of the acid used, the pH of 3.5 appears to be too low for egg hatch, larval viability, egg-to-pupa recovery, and pupal weight.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For both species of fruit fly, the smaller viability of the larval and pupae stage observed when larvae were kept on diet with pH 2.0, but differing from the diet with pH 3.0, is similar to results reported for Bactrocera invadens Drew, Tsuruta & White, 2005 (Diptera: Tephritidae) using liquid diet with pH 3.5 Ekesi et al (2014). Vera et al (2014) evaluated diets for A. fraterculus with addition of ascorbic, citric and lactic acid and found that, irrespective of the acid used, the pH of 3.5 appears to be too low for egg hatch, larval viability, egg-to-pupa recovery, and pupal weight.…”
Section: Discussionsupporting
confidence: 82%
“…Vargas et al (1984), found rapid deterioration in artificial diets with pH between 5.0 and 6.0. Vera et al (2014) found contamination on diets for larval development with pH 4.5. On diets with pH 1.5 and 1.0, there was no contamination and no larval hatching either, which may be related to the infertility of eggs on the acid medium (Von Zuben, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, B. dorsalis (Chang, Vargas, Jang, Caceres, & Cho, ) and Ceratitis capitata Wiedemann (Chang, Caceres, & Ekesi, ) were successfully reared with the liquid larval diet. More recently, liquid artificial diet has been used to rear a number of tephritid fruit fly species including Anastrepha fraterculus Wiedemann (Vera et al., ) and also other Diptera including Musca domestica L. (Chang, ). Only one attempt has been made to rear a member of the genus Dacus ( Dacus ciliatus Loew) using the liquid diet (Chang, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, liquid artificial diet has been used to rear a number of tephritid fruit fly species including Anastrepha fraterculus Wiedemann (Vera et al, 2014) and also other Diptera including Musca domestica L. (Chang, 2008). Only one attempt has been made to rear a member of the genus Dacus (Dacus ciliatus Loew) using the liquid diet (Chang, 2008).…”
Section: Introductionmentioning
confidence: 99%